Peran Keluarga, Sekolah dan Masyarakat dalam Penanganan Kekerasan Terhadap Anak (Child Abuse) pada Masa Pandemi COVID-19 - ' Ririen Arinalhaq, Hadiyanto (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
This paper is based on the problem that there has been an increase in violence against children during the pandemic of the corona viruse desease-19 which is popular with covid-19. The review begins with the development of Covid-19 in Indonesia and the world and is continued with Covid-19 on violence perpetrated by the environment against children. Children are entrusted by the Almighty who must be cared for and considered for their growth and development. It is not uncommon for violence against children from adults to be broadcast on mass media or social media in the form of physical violence